Pembinaan Kompetensi Sebagai Upaya Meningkatkan Kinerja Tenaga Administrasi Sekolah - Nuraini Nuraini; Afriza Afriza; Tuti Andriani (Dinasti Review, 2022)
Abstract: This study aims to analyze competency development as an effort to improve the performance of school administration staff. The research method used is library research or library research. The data analysis technique used is content analysis. The results of the study show that school administrative staff are educational staff whose job is to provide support for administrative services for the implementation of the educational process in schools. Performance or performance of administrative personnel is the result of work that can be achieved by administrative staff in the form of providing services to parents of students and the community by their respective responsibilities and authorities to achieve the vision, mission, and goals of the school, and achieve the goals of school administration services only possible because of the efforts of administrative personnel. Abstrak: Penelitian ini bertujuan untuk menganalisa pembinaan kompetensi sebagai upaya meningkatkan kinerja tenaga administrasi sekolah. Metode penelitian yang digunakan adalah penelitian kepustakaan atau library research. Teknik analisis data yang digunakan adalah analisis konten atau content analysis. Hasil penelitian menunjukkan bahwa Tenaga administrasi sekolah adalah tenaga kependidikan yang bertugas memberikan dukungan layanan administrasi guna terselenggaranya proses pendidikan di sekolah. Kinerja atau performance tenaga administrasi adalah hasil kerja yang dapat dicapai oleh tenaga administrasi dalam bentuk pemberian layanan pada orang tua siswa dan masyarakat sesuai dengan tanggungjawab dan wewenang masing-masing dalam upaya mencapai visi, misi dan tujuan dari sekolah, serta tercapainya tujuan layanan administrasi sekolah hanya dimungkinkan karena adanya upaya tenaga administrasi.